EFEKTIVITAS PENYIDIK BADAN NARKOTIKA NASIONAL SUMATERA UTARA DALAM PEMBERANTASAN TINDAK PIDANA NARKOTIKA - Maria Polla Manalu; Nurmaya R A Simanjuntak (JOURNAL OF LAW AND NATION, 2025)
Narcotics abuse has become a serious problem that threatens the young generation and the stability of countries, including in Indonesia. Etymologically, narcotics comes from the Greek term "narke" which refers to the effects of anesthesia and loss of sensation. Narcotics abuse not only impacts an individual's physical and mental health, but also triggers social, economic and legal losses. Law Number 35 of 2009 defines narcotics as substances or drugs that can cause changes in consciousness, loss of pain, and cause dependence.In Indonesia, the circulation of narcotics continues to increase along with advances in technology and information that make it easier to distribute them illegally. The National Narcotics Agency (BNN) has a strategic role in eradicatin.